HASIL BELAJAR KOGNITIF SISWA KELAS X MELALUI PENERAPAN MODEL PEMBELAJARAN PEER LED GUIDED INQUIRY (PLGI) PADA MATERI IMPULS DAN MOMENTUM DI SMAN 3 PEKANBARU - Pohan, Dhesy Fansury; Azhar, Azhar; Azizahwati, Azizahwati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aimed to know the result study of students’ physics cognitive by applying Peer Led Guided Inquiry (PLGI) learning model. This research was conducted in SMAN 3 Pekanbaru. It was a pre-eksperimental research with intact group comparison design. The subject of this research was student of X MIA 5 as experimental class and student of X MIA 3 as control class. The data collection conducted by using a test from the result study of students’ cognitive after applying Peer Led Guided Inquiry (PLGI) learning model in the experimental class and conventional learning in control class. The technique of analysis technique was used to know the description of the students’ learning outcomes including the students’ absorption and the effectiveness of the learning. The result of this research showed the average of students’ absorption by applying the Peer Led Guided Inquiry (PLGI) learning model was 82.48% and the average of students’ absorption by applying conventional learning was 74.10%. it concluded that applying Peer Led Guided Inquiry (PLGI) could improve the result of students’ cognitive on impulse and momentum material at the X Grade of SMAN 3 Pekanbaru.Keywords: Peer Led Guided Inquiry (PLGI), Result Study Of Students’ Cognitive,Impulse and momentum.